Compilation of Islamic Law as a Product of State Ijtihad: Analysis of its Position and Implementation in the Indonesian Legal System - Abdul Rahman; Muhammad Sopyan; Khairuddin Hasibuan (ISNU Sumatera Utara, 2026)
This study examines the Compilation of Islamic Law (KHI) as a product of state ijtihad and analyzes its position and implementation in the Indonesian legal system. The background of this study is the need for harmonization between sharia norms and national law, amidst the complexity of modern society that demands legal certainty and substantive justice. The objectives of the study are to examine the position of the KHI in the national legal hierarchy, assess the effectiveness of its implementation in Religious Courts, and identify criticisms and challenges that arise in the context of contemporary social and legal developments. This study uses a normative legal research method with a statutory and conceptual approach through a literature review of laws and regulations, Islamic legal literature, fatwas of scholars, and related academic documents. The analysis is conducted descriptively and qualitatively to assess the position, relevance, and adaptability of the KHI in judicial practice. The results show that the KHI occupies a strategic position as an instrument for harmonizing Islamic law with national law, providing uniform guidelines for judges, and ensuring legal certainty. The implementation of the KHI has succeeded in delivering substantive justice through contextual interpretation, despite facing challenges from social change, human rights, and modern family dynamics. Critics of the KHI emphasize the need for text adaptation, socialization, and periodic revision to maintain its relevance. In conclusion, the KHI serves as a living legal instrument, integrating sharia principles, legal certainty, and societal interests. The study recommends regular evaluation, capacity building for judges, and contextual interpretation mechanisms to ensure the KHI remains effective and responsive to the needs of modern society.